Correlation of HbA1c Levels with Severity of Diabetic Retinopathy (Community Based Medical Journal, 2026)
Diabetic retinopathy (DR) is a leading microvascular complication of diabetes mellitus and a major cause of preventable visual impairment. Glycated hemoglobin (HbA1c) reflects long-term glycemic control and is considered a key predictor of diabetic complications. However, data correlating HbA1c levels with the severity of DR in Bangladeshi patients remain limited. A prospective, cross-sectional study was conducted in Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, from January 2023 to December 2024, to see the correlation between HbA1c levels and the severity of diabetic retinopathy in Bangladeshi patients. A total of 46 patients with diabetes mellitus were enrolled using purposive sampling. HbA1c levels were measured using standardized laboratory methods. A total of 46 patients with diabetes mellitus were included in the study. The mean age of the patients was 54.2±9.6 years; male-female ratio was 1.42:1. The mean duration of diabetes was 8.7±4.1 years. Regarding glycemic status, the mean HbA1c level was 8.4±1.6%. The majority of the patients (56.5%) had poor glycemic control (HbA1c ≥8.0%), while only 17.4% had HbA1c levels